Early‐Career Scientists Discuss Research and Future Directions for the Paleoclimate Field: Second PAGES Young Scientists Meeting: The Past—A Compass for Future Earth; Goa, India, 10–12 February 2013. (25th June 2013) - Bogus, Kara; Bouimetarhan, Ilham; Richey, Julie
Abstract : Projections of future climate and environmental change are largely dependent on reconstructions of Earth's climate. Paleoenvironmental studies are a key element in scientists' understanding of how the global hydrological cycle, oceanic and atmospheric circulation, and marine and terrestrial ecosystems respond to climate forcing, such as increased atmospheric carbon dioxide concentration. Despite many advances in the field of paleoclimatology, there are still large uncertainties in proxy calibration, chronology, and paleoclimate models that need to be addressed.